C‐reactive protein and incidence of type 2 diabetes in the Pizarra study. (20th December 2012) - Rubio‐Martín, Elehazara; Soriguer, Federico; Gutiérrez‐Repiso, Carolina; Garrido‐Sánchez, Lourdes; de, Marisol S. Ruíz; García‐Fuentes, Eduardo; Morcillo, Sonsoles; Esteva, Isabel; Chaves, Felipe J; Rojo‐Martinez, Gemma
Abstract Aim To determine the association between serum levels of high‐sensitivity C‐reactive protein (hs‐CRP) and the incidence of type 2 diabetes in a prospective cohort from southern Spain (Pizarra study). Materials and methods The study formed part of the Pizarra cohort study, a prospective study started in 1995 with a follow‐up of 11 years. Anthropometric and metabolic variables were measured at baseline and at 6 years and 11 years of follow‐up. All subjects underwent an oral glucose tolerance test. Serum levels of TNFα and its receptors, hs‐CRP, IL‐6, leptin, adiponectin and FABP4 were measured at 6 years of follow‐up. Results After adjusting for age, sex and obesity, subjects with levels of hs‐CRP> 2.9 mg/L in the second study (2003–4) had a higher risk of developing type 2 diabetes by the third study (2008–9) (OR = 7.97; 95% CI = 1.72–36.89; P = 0.008), and subjects with adiponectin levels > 13.2 mg/L had a lower risk of developing type 2 diabetes (OR = 0.23, P = 0.02). High values of hs‐CRP and high values of adiponectin were associated positively (OR = 8.26; 95% CI = 1.84–37.19; P = 0.006) and negatively (OR = 0.17; 95% CI = 0.04–0.69; P = 0.01), respectively, with the risk of having HbA1c ≥ 6.5% at 11 years of follow‐up. Conclusions Subjects with high serum hs‐CRP levels and low serum adiponectin levels have a higher risk of developing type 2 diabetes within five years.